Mental perception and its relationship to achievement motivation among Kirkuk club players in fencing (Journal of the College of Basic Education, 2022)
The research aims to identify the level of mental perception and achievement motivation for fencing players, in addition to identifying the relationship between mental perception and achievement motivation for fencing players. The hypothesis of the research is the existence of a moral confusion relationship between the mental perception and achievement motivation for the fencing players. The research problem was to answer the following question: What is the level of mental perception and achievement motivation that fencing players have? . The research sample was represented by the (6) players of fencing for Kirkuk clubs, as questionnaires were distributed to them and statistical means were extracted. The researcher reached a set of results, including that the fencing players were distinguished by a high level of mental perception and achievement motivation, and that the greater the mental perception, the greater the achievement motivation of the players. The researcher recommended conducting studies similar to the current study on team games and working on studies related to mental perception and paying more attention to the psychological aspect.